A study on the administration of mutual aid funds for board members Case study: Nan District, Luang Prabang Province - XIONG, Mee; HOONGSENGPHA, Soudthida; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The study aimed to collect the opinions of union members who have joined the fund on the management of the fund by the director board, this research was used questionnaire as a tool to collect data from 265 fund members in Nan District, Luang Prabang Province, with a confidence value of 0.977. Data analysis was based on the mean and standard deviation. The study found that: The group who responded was found the female more than male, most of the members were between 34 - 41 years old and lowest of group was more than 58 years old and most of them were married. As for the members opinions on the management of the mutual aid fund management board, overall mean was good level such as: planning, structure, personnel management and employee performance, budget management. Overall, the performance is seen to be good, with only the coordination having mean value of medium/adequate. In addition, the fund structure and finally the overall implementation results are seen to be good.